2019
DOI: 10.21037/atm.2019.07.102
|View full text |Cite
|
Sign up to set email alerts
|

Screening and combining serum biomarkers to improve their diagnostic performance in the detection of intestinal barrier dysfunction in patients after major abdominal surgery

Abstract: Background: The aim of this prospective study was to screen and combine effective biomarkers to improve their diagnostic performance in detecting intestinal barrier dysfunction in patients after major abdominal surgery. Methods: Patients undergoing major abdominal surgery were enrolled after signing informed consent in this study. The serum concentrations of α-GST, DAO, D-lactate, citrulline and I-FABP were detected 24 hours before and after surgery. The diagnostic performance of five biomarkers on intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
1
10
0
1
Order By: Relevance
“…Several circulating biomarkers have been tested and validated for the assessment of intestinal barrier integrity and bacterial translocation. Intestinal fatty acid-binding protein (I-FABP) and diamine oxidase (DAO) are cytosolic proteins in intestinal epithelial cells and are immediately released into the circulation when the intestinal epithelium is disrupted ( 14 , 15 ). Zonulin, the only known physiological regulator of intestinal permeability, reversibly opens tight junctions between intestinal epithelial cells ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several circulating biomarkers have been tested and validated for the assessment of intestinal barrier integrity and bacterial translocation. Intestinal fatty acid-binding protein (I-FABP) and diamine oxidase (DAO) are cytosolic proteins in intestinal epithelial cells and are immediately released into the circulation when the intestinal epithelium is disrupted ( 14 , 15 ). Zonulin, the only known physiological regulator of intestinal permeability, reversibly opens tight junctions between intestinal epithelial cells ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, D-lactic acid is seldom present in the intestinal lumen, and its concentration could signal initial damage to the intestinal barrier. In our study, we found that GA could significantly reduce the levels of D-lactose, a reliable biomarker of intestinal permeability (26). Similarly, since only a small proportion of lactulose could permeate through the intestinal mucosa, while mannitol could always pass through, intestinal permeability can be measured by detecting the LMR in the urine (27).…”
Section: Discussionmentioning
confidence: 57%
“…Serum biomarkers that reflect damage of the intestinal mucosal barrier have been identified in several clinical and animal studies [4]. Peters et al 1989 [8] and Khurana et al 2002 [9] examined the activity of GST enzymes in the small and large intestines and proved that intestinal epithelial cells have a high content and activity of cytosolic GST and when the cell membrane of intestinal epithelial cells is damaged, these enzymes are released and their serum levels correlate with the degree of intestinal epithelial damage.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal epithelial barrier dysfunction increases intestinal mucosal permeability. As a result, intestinal bacteria, endotoxins, and other harmful substances pass through the intestinal tissue and initiate a series of pathophysiological changes and even a systemic inflammatory response and multiorgan dysfunction syndrome [4]. Although there has been progress in tests that assess the function of the intestinal epithelial barrier, the evaluation of the integrity and function of the intestinal epithelium for clinicians remains challenging [3].…”
Section: Introductionmentioning
confidence: 99%